Application of Digital Image Processing Technique in Monitoring LNAPL Migration in Double Porosity Soil Column - Ngien, S. K.; R., Sa'ari; N. A., Rahman; H. N., Abdul Latif; Z. M., Yusof; S. A., Kamaruddin; M., Mustaffar; M. A., Hezmi (Penerbit Universiti Teknologi Malaysia, 2015)
This paper investigates the phenomenon of light non-aqueous phase liquid (LNAPL) migration in double porosity soil. Investigation on the migration of LNAPL in double porosity soil was performed on aggregated kaolin using the digital image analysis. The photographic technique was used to capture the migration of LNAPL in aggregated soil samples. The captured digital images were fed through an image processing code to convert them to the hue-saturation-intensity (HSI) format which were subsequently used to plot the 2D LNAPL migration behaviour. The results of Experiment 1 and 2 show that the LNAPL moved downward faster when the moisture content increased. Another observation was that the kaolin granules started to disintegrate at a water content of 35%. In conclusion, using image analysis technique has enabled the researchers to monitor and visualize the LNAPL migration in the double porosity soil columns based on HSI values. The contour plots of HSI intensity value has provide detailed and useful information for future research.